People's Republic of China-Hong Kong Special Administrative Region : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This Selected Issues paper for the People's Republic of China-Hong Kong Special Administrative Region (SAR) reviews the residential property market and implications of an aging population. The fiscal sector impact of price fluctuations is important in Hong Kong SAR with land sales and stamp duties providing an important source of government revenue. The simulations are based on a dynamic general equilibrium system with forward-looking behavior and rational expectations. Hong Kong SAR's revenue flows are characterized by relatively volatile nontax items.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet